Le musée comme outil de remédiation identitaire : Le cas du Louvre-Lens - Maia Morel (Midas: Museus e Estudos Interdisciplinares)
From its inception, the museum has continuously developed its educational ambitions and actions. If it no longer has its former role of national glorification, it remains however a strong support to identity. We consider from that perspective the establishment of a branch of the Louvre Museum in Lens, a region of France, hard-hit by the industrial crisis, with a durable local identity, experiencing a strong feeling of marginalisation. Symbolically, the museum reaches out to residents by settling on the former location of its once very active industrial activity. However, it presents an extremely consensual vision of Art, through a careful selection of works, all of them legitimized by the fact that they come from the Louvre. They are presented in a chronological sequence, from Antiquity to the early nineteenth century that is to say to the Industrial Revolution. The visitor is thus invited to discover the history of humanity seen through a national vision (given by the Louvre) and to link it to his own history.